A remark on weighted averages for superadditive processes - Dogan Cömez (International Journal of Mathematics and Mathematical Sciences)
A decompostion of a superadditive process into a difference of an additive and a positive purely superadditive process is obtained. This result is used to prove an ergodic theorem for weighted averages of superadditive processes.